Exploration of Symbiotic Bacteria with the Potential to Degrade Chlorpyrifos Insecticide in the Digestive Tract of the Beet Armyworm (Spodoptera exigua) (Lepidoptera: Noctuidae) in Shallot Fields, Probolinggo - SyamsulHadi, Mochammad; Restikasari, Viera Annisa; Taufiqurrahman, Achmad Fitriadi; Widjayanti, Tita (Plantropica: Journal of Agricultural Science, 2024)
The beet armyworm, Spodoptera exigua is a notorious pest that inflicts significant damage to shallot crops, especially leeks, causing leaves to wither due to brown spots and transparency. This issue often leads to excessive chemical control measures, which, in turn, promote insecticide resistance. This study hypothesized that symbiotic bacteria within S.exigua have the capacity to degrade chlorpyrifos-based insecticides. S.exigua samples were collected in Dringu, Gending, and Leces districts, Probolinggo, and subsequently examined for symbiotic bacteria with biodegradation potential. Bacterial exploration and identification were conducted from April to October 2023 at the Pesticide Toxicology Laboratory, Brawijaya University. The study analyzed the clear zone diameter produced by bacteria in media contaminated with chlorpyrifos-based insecticides as an indicator of biodegradation. Out of 41 surviving bacterial isolates, 10 demonstrated notable biodegradation capabilities. The Genus identification revealed that Erwinia sp., Pantoea sp., and Coryneform sp. were among the contributing bacteria. This research emphasizes the potential role of S.exigua-associated symbiotic bacteria in managing chlorpyrifos-resistant pest populations, offering a promising avenue for sustainable pest control methods.